INTERNALIZATION PROCESS OF REASONING AND PROOF STANDARDS FOR ELEMENTARY SCHOOL TEACHERS IN MATHEMATICS LEARNING - Awal Nur Kholifatur Rosyidah; Umar Umar; Iva Nurmawanti; Vivi Rachmatul Hidayati; Mohammad Archi Maulyda (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Reasoning and Proof ability are one of the five standards in NCTM. Its implementation in learning can be transformed into problem-based learning (PBL). The purpose of this study is to provide a description related to the internalization of Reasoning and Proof standards in the mathematics learning process in elementary schools. The type of research used is qualitative with descriptive analysis. The research subjects were 24 elementary school teachers in Cluster IV Mataram City. The data collection process was carried out by a survey method that was conducted online using the Google form platform. To strengthen the results of the questionnaire, interviews were also conducted via WhatsApp phone to each research subject. The results of the research showed that 45.8% (11 subjects) had never heard of the terms reasoning and proof, while 54.2% (13 subjects) had never heard of the terms reasoning and proof. The deepening of the results of this study found that the feasibility of Reasoning and Proof standards in learning was still not optimal. In addition, several interesting facts were found related to the method of proof that teachers often use, namely giving examples that are close to students (relate).